Die zervikale spondylotische Myelopathie: Indikationsstellung für eine chirurgische Therapie - Pepke, Wojciech; Al Mansour, Haidara; Richter, Marcus; Akbar, Michael (Der Orthopäde, 2018)
BackgroundThe pathogenesis of cervical spondylotic myelopathy (CSM) is often multifactorial. Hence, the treatment of this disease requires a differentiated surgical approach in order to adequately address the underlying pathology.PurposeThe aim of this review is to identify factors that influence the choice of treatment strategy and to summarize them in an algorithm that serves as a decision aid in choosing the optimal indication for surgical treatment. An attempt is made to define the threshold values for the indication of surgical treatment and to discuss the ideal timing for performing surgery.Materials and methodsOn the basis of the published data, the influencing factors on the prognosis of CSM, as well as surgical approaches are discussed.ResultsCircumferential spinal cord compression, a sharply defined myelopathy signal in the T2-weighted MRI sequence, and segmental instability at the level of the myelopathy signal mean an unfavorable prognosis for the worsening of CSM. The most important factors that influence the choice of the surgical access point are the sagittal profile of the cervical spine, the extent of myelopathy, the extent of stenosis, and the location of the myelopathy-inducing pathology. Previously existing neck pain and prior cervical surgery must also be considered.DiscussionOn the basis of the research carried out, we developed an algorithm that could serve as an aid in choosing the right treatment in the setting of cervical spondylotic myelopathy.